2018
DOI: 10.3390/f9060354
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physicochemical Changes of Carpinus betulus L. Influenced by Salinity Treatments

Abstract: Carpinus betulus L. is a deciduous tree widely distributed in Europe with strong adaptation, and it plays a key role in landscaping and timbering because of its variety of colors and shapes. Recently introduced to China for similar purposes, this species needs further study as to its physiological adaptability under various soil salinity conditions. In this study, the growth and physicochemical changes of C. betulus seedlings cultivated in soil under six different levels of salinity stress (NaCl: 0, 17, 34, 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Increasing evidence points to the involvement of ROS in salt stress response mechanisms and salinity tolerance 14 , 63 . K + –Na + ratios have also been shown to decrease in salinity in many plant species, both herbaceous 54 , 64 and woody 44 , 65 . Under typical physiological conditions, plants maintain a high cytosolic K + –Na + ratio, which is necessary for optimal plant growth and leaf photosynthesis 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence points to the involvement of ROS in salt stress response mechanisms and salinity tolerance 14 , 63 . K + –Na + ratios have also been shown to decrease in salinity in many plant species, both herbaceous 54 , 64 and woody 44 , 65 . Under typical physiological conditions, plants maintain a high cytosolic K + –Na + ratio, which is necessary for optimal plant growth and leaf photosynthesis 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Salinity stress can cause the close of stomata, the decrease of stomatal size and leaf thickness, and the atrophy of leaf tissues [42]. In our previous study on Carpinus betulus L. [43], we found the stomata, palisade, and spongy parenchyma tissues were seriously influenced over 51 mM NaCl, worse than C. turczaninowii. These changes in leaf morphology can adversely affect photosynthesis in plants.…”
Section: Seedling Growthmentioning
confidence: 96%
“…An overabundance of ROS, which cannot be compensated by antioxidative systems, leads to damage symptoms such as chlorophyll degradation, membrane leakage, and eventually necrosis [13]. Some examples for salt damage symptoms at the tissue and organelle levels are also demonstrated in this Special Issue [14,15]. Since soil degradation with enhanced salinization is an increasing problem, identification of salt-tolerant plant species and measures to enhance the resistance of crops and horticultural plants are urgently needed.…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 99%
“…Hornbeam (Carpinus turczaninowii) is known for its beautiful autumn colors and fine-textured wood. Zhou et al [15,17] systematically tested the performance of this tree species as well as its European counterpart Carpinus betulus under moderate salt stress (up to 85 mM). They found that antioxidant systems of the European species collapsed after about 1 month and that of the Asian species after about 2 months in the presence of low salinity levels (30 to 50 mM).…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 99%